Weaning and associated factors in children from low-income communities - Anyele Kleine BUCKSTEGGE; Luciana Reichert da Silva ASSUNÇÃO; Fernanda de Morais FERREIRA; Fabian Calixto FRAIZ; Margaret Cristina da Silva BOGUSZEWSKI
Introduction: The average duration of breastfeeding is still insufficient and differ widely taking in account the location and specific characteristic of local people involved in these studies. Aim: This research aimed at studying factors associated to weaning among South Brazilian children living in a low-income household. Material and method: Cross-sectional study was carried out enrolling 124 mothers of 1 to 12-month-old children, who were interviewed at "Pastoral da Criança" (non-governmental organization) in Almirante Tamandaré, Paraná, Brazil. The risk of weaning considered was the dependent variable and the information collected from the questionnaires, independent variables. The method used to collect information in this study was Kaplan-Meier method and Cox regression model and Spearman's rank correlation (α = 0.05). Result: Actuarial life table presented a higher weaning conditional probability at 12 months of age, followed by first and fourth months of age. Multivariate analysis pointed out that contact with bottle feeding before the sixth month of age [HR=17.16 (2.34-125.86)] and contact with pacifier before the sixth months of age [HR=3.48 (1.90-6.38)] are risk factors associated with weaning. Among children who were not breastfed at the moment of the interview, breastfeeding duration presented a positive correlation with the ages when the children had their first contact with sugar (r s =+0.419, p=0.001) and negative correlation with the use of pacifier (r s =-0.300, p=0.017). Conclusion: Results from this study showed that the use of the feeding bottle and pacifier were related to a shorter breastfeeding time span at these communities.